THE INFLUENCE FROM FINANCIAL PERFORMANCE ON EARNING PER SHARE (EPS) WITH SOUNDNESS LEVEL OF BANKS AS INTERVENING VARIABLE AT BUKU IV BANKS CATEGORY IN INDONESIA - Rosmery Thomas; Selamet Riyadi; Zaenal Abidin; Muhammad Iqbal (Dinasti International Journal of Education Management And Social Science, 2020)
The purpose of this research was to analyze those influence of financial ratios towards earnings per share with soundness level of banks as an intervening variable based on risk-based bank rating method at BUKU IV Banks in Indonesia for the period of 2015-2019. The six banks are PT Bank Mandiri Tbk, PT Bank Rakyat Indonesia Tbk, PT Bank Negara Indonesia Tbk, PT Bank Central Asia Tbk, PT Bank CIMB Niaga Tbk and PT Bank Danamon Indonesia Tbk. This research used secondary data with quantitative approach. Data analysis technique used panel data regression by purposive sampling. The results showed that NPL & GCG had significant negative influence on soundness level of banks and NPL had significant negative impact on EPS. GCG had significant positive influence against EPS, and ROA & CAR did not have significant positive impact towards soundness level of banks & EPS, while soundness level of banks were not found to have significant negative affect to EPS, and soundness level of banks did not mediate NPL, GCG, ROA and CAR in affecting EPS